Implementasi Fatwa Dewan Syariah Nasional tentang Al-Ijarah Al Muntahiya Bi Al Tamlik di Baitul Tamwil Muhammadiyah - Sabil, Daffi; Pratami, Bunga Desiana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Ijarah muntahiya bittamlik is a lease agreement that involves a transfer of ownership at the end of the lease period. Ijarah muntahiya bittamlik aims to obtain the opportunity to obtain the right to control goods in terms of using the ijarah muntahiya bittamlik agreement. The purpose of the study discuss the implementation of the ijarah muntahiya bittamlik agreement, whether it is under the National Sharia Council Fatwa Number 27 / DSN-MUI / III / 2002. This study is a type of empirical juridical research, with a qualitative approach. Data sources consist of primary data obtained by observation and interview techniques with parties who make contracts at Baitut Tamwil Muhammadiyah (BTM) Pekalongan Regency. Secondary data in the form of research journals, books, and research results that are relevant to this study. Data is analyzed using qualitative descriptive techniques. The results of the study indicate that the ijarah muntahiya bittamlik agreement at BTM Kajen is generally by the National Sharia Council Fatwa Number 27 / DSN-MUI / III / 2002. However, specifically, its implementation in BTM Kajen is to carry out a sale and purchase agreement first to be used as the object of the ijarah muntahiya bittamlik agreement, then carry out the ijarah and ijarah muntahiya bittamlik agreements. Meanwhile, the Fatwa of the National Sharia Council states that the party carrying out the ijarah muntahiya bittamlik agreement must carry out the ijarah agreement first before carrying out the sale and purchase.